Pengenalan Angka Dalam Bahasa Arab Kepada Anak Usia Dini di PAUD Al-Fatih Desa Lubuk Keliat - Desi Fitriyana; Fardhaniyah Utaminingsih (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This community service program in the form of education is based on the collaboration between students of Real Work Lecture Raden Fatah Palembang State Islamic University with Lubuk Keliat Village, Lubuk Keliat District, Ogan Ilir Regency, South Sumatera Province to provide teaching related to the introduction of numbers in Arabic to young children (AUD) amounting to 30 people. The aim of this service is to introduce numbers in Arabic to young children at Al-fatih preschool, Lubuk Keliat Village, Lubuk Keliat District.